Tricomi problem for an elliptic-hyperbolic equation of the second kind - Mamadaliev, Nazirjon Kamildjanovich (Eurasian Mathematical Journal, 2014)
Unique solvability of the Tricomi problem for an elliptic-hyperbolic equation of the second kind is proved with the help of the representation of the generalized solution to a hyperbolic equation with strong degeneration.